2016
DOI: 10.1210/jc.2015-4091
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Glucose Oxidation, Reduced Insulin Secretion, and a Fatty Heart May Be Protective Adaptions in Ischemic CAD

Abstract: Background:Insulin resistance, β-cell dysfunction, and ectopic fat deposition have been implicated in the pathogenesis of coronary artery disease (CAD) and type 2 diabetes, which is common in CAD patients. We investigated whether CAD is an independent predictor of these metabolic abnormalities and whether this interaction is influenced by superimposed myocardial ischemia.Methods and Results:We studied CAD patients with (n = 8) and without (n = 14) myocardial ischemia and eight non-CAD controls. Insulin sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
(64 reference statements)
1
6
0
Order By: Relevance
“…In the present study, we did not measure a degree of ischemia but all the participants with CAD were in a stable condition. Nonetheless, our data obtained by direct measurement of the triacylglycerol content in the myocardium of the patients with multivessel coronary artery disease are in line with the above-mentioned report [36].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we did not measure a degree of ischemia but all the participants with CAD were in a stable condition. Nonetheless, our data obtained by direct measurement of the triacylglycerol content in the myocardium of the patients with multivessel coronary artery disease are in line with the above-mentioned report [36].…”
Section: Discussionsupporting
confidence: 92%
“…Recently, it was shown that myocardial TG content was elevated in patients with ischemic CAD in relation to patients with nonischemic CAD. The degree of ischemia was evaluated with the PET/CT technique [36]. In the present study, we did not measure a degree of ischemia but all the participants with CAD were in a stable condition.…”
Section: Discussionmentioning
confidence: 95%
“…72 Both glucose uptake and insulin signaling are impaired in diseases such as coronary heart disease and heart failure. 71,73 Likewise, additional pathways relevant to cardiac development and function were identified by GREAT analysis, including PI3K pathway function (female, hypomethylated) and embryonic heart tube morphogenesis (male, hypermethylated). The PI3K pathway plays an important role in regulation of cardiac hypertrophy and contractility, and altered function of this pathway is implicated in heart failure and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients in class 3 were less likely to have hypertension and diabetes, but their blood pressure and glucose level were significantly higher than those in class 1 and class 2 after admission, indicating that the increase in blood pressure and glucose level might be associated with the stress response. It has been reported that glucose oxidation is enhanced in CAD patients under stress, which could further prevent insulin secretion [17]. AKI in CAD patients after left cardiac catheterization might be associated with contrast nephropathy [18] and ischemic nephropathy [19].…”
Section: Discussionmentioning
confidence: 99%